2011
DOI: 10.1007/s00125-011-2232-3
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 (GLP-1) and the regulation of human invariant natural killer T cells: lessons from obesity, diabetes and psoriasis

Abstract: Aims/hypothesisThe innate immune cells, invariant natural killer T cells (iNKT cells), are implicated in the pathogenesis of psoriasis, an inflammatory condition associated with obesity and other metabolic diseases, such as diabetes and dyslipidaemia. We observed an improvement in psoriasis severity in a patient within days of starting treatment with an incretin-mimetic, glucagon-like peptide-1 (GLP-1) receptor agonist. This was independent of change in glycaemic control. We proposed that this unexpected clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
148
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(170 citation statements)
references
References 50 publications
15
148
1
3
Order By: Relevance
“…Although GLP-1 increased cytokine production in resting iNKT cells, both GLP-1 and liraglutide inhibited cytokine secretion following treatment with phorbol myristate acetate/ionomycin, or in iNKT cells activated by co-culture with glycolipidtreated CD1d-transfected C1R cells, actions blocked by the GLP-1R antagonist exendin (9-39). Hence, the authors infer that the putative immunoregulatory actions of GLP-1 on iNKT cells may have contributed to the improvement in clinical psoriasis observed in the three patients [2].…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…Although GLP-1 increased cytokine production in resting iNKT cells, both GLP-1 and liraglutide inhibited cytokine secretion following treatment with phorbol myristate acetate/ionomycin, or in iNKT cells activated by co-culture with glycolipidtreated CD1d-transfected C1R cells, actions blocked by the GLP-1R antagonist exendin (9-39). Hence, the authors infer that the putative immunoregulatory actions of GLP-1 on iNKT cells may have contributed to the improvement in clinical psoriasis observed in the three patients [2].…”
mentioning
confidence: 95%
“…Pioglitazone has been shown to exert an anti-psoriatic effect when co-administered with the synthetic retinoid acitretin to non-obese non-diabetic participants with moderate to severe plaque-type psoriasis in a 12 week randomised clinical trial [12]. In the patients reported by Hogan et al, the improvement in psoriasis was relatively rapid following the initiation of treatment with exenatide or liraglutide, with no significant improvement in glycaemic control noted [2]. Although the reductions in PASI score were modest, they occurred rapidly, and psoriasis does not usually improve spontaneously without therapy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…al. [2] reported that the psoriasis area and Severity Index improved in 2 psoriatic patients treated with glucagon-like peptide-1 (GLP-1) and clinical improvement was associated with an increase in circulating NKT cells and a decrease in the psoriatic lesions compared to counts prior to treatment. The use of GLP-1 for the treatment of psoriasis was suggested.…”
Section: Natural Killer T Cells (Nkt) and γ/δ T-cellsmentioning
confidence: 99%